Witchcraft in Print in Early Modern Germany and England - Natalie, Grace (2023)
This thesis is a comparative study of witchcraft in German and English print, c. 1560-1690. There is a wealth of research on witchcraft in each country, much of which has been conducted through regional studies. This approach is logical because of the complexity of the witch-hunts and witch beliefs, but historians are increasingly seeking alternative methodologies to build a bigger picture. This thesis addresses this need. Chapter One introduces the primary sources: these fall under the broad category of ‘popular print’, including broadside ballads, single-sheet broadsheets, occasional news pamphlets, religious tracts, and sermons. It also examines the notion of ‘popular print’ and explores the intended purpose of these sources. Chapter Two compares how components of the ‘cumulative concept’ and ‘elaborated concept’ of witchcraft were addressed in the two countries. Chapter Three investigates the legal context that underpinned the trials, explores attitudes towards the crime of witchcraft in print, and contextualises these sources within the wider crime reporting genre. Chapter Four analyses the witch identity and its construction in print and evaluates whether witch tropes changed during times of crisis. Chapter Five inspects the ways that location shaped printed witchcraft narratives, including the transmission of information across national borders and spaces associated with the supernatural. Through its thematic approach, this thesis contributes to several fields alongside witchcraft including print culture, gender and identity, and criminality. Overall, the thesis reveals commonalities between German and English witchcraft discourses which have not been recognised previously. It also proposes that differences were due – at least in part – to the organisation and structure of the printing industries and literary conventions in each country. Ultimately, this thesis demonstrates the value of moving beyond local, regional, and even national borders, and argues that a balanced and sustained comparison of two countries yields new and important perspectives for witchcraft studies.